Single Stage Transanal Pull through in patients with Short Segment Hirschprung’s Disease-Our Experience with Swenson Technique - IRAM UZMA KHALID; KHADIJA TUL KUBRA; MUHAMMAD AMIR HANIF KHAN (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To study the results of primary transanal pull-through in the patients of short-segment Hirschsprung’s disease (HD) without using the frozen section facility. Patients and methods: This retrospective cohort study was performed in the Department of Paediatric Surgery, Nishtar Medical University, Multan, from January 2021 to December 2023. Thirty-five patients of more than one year of age, diagnosed with short segment HD based on history, examination, barium enema, and rectal biopsy, were included in the study. Patients having HD with any syndrome or with stoma were excluded from the study. One-stage transanal Swenson pull-through was performed, and the transition zone was identified on naked-eye visualization. No frozen section facility was used. Patients were followed for six months for complications and outcomes. Results: Out of 35 patients, 8 (22.8%) had a total of 11 complications. Enterocolitis was most frequent, seen in 3 (8.6%) patients. Other complications included anastomotic stricture, anastomotic leakage, constipation, fecal incontinence, and abdominal distension. Two biopsies showed an absence of ganglion cells, and it was significantly associated with complications (p-value .007). Two patients needed diversion stoma. Overall, 27 (77.14%) patients showed good results post-operatively. Conclusion: Primary transanal endorectal pull-through can be performed safely in children with short-segment HD without the use of frozen section facilities. Careful identification of the transition zone during the surgery is important, as inadequate resection can result in multiple complications. However, most of the complications can be managed conservatively. Keywords: Hirschsprung’s disease, Transanal pull through, Frozen section, Enterocolitis.